Soft thermoplastic elastomer composition and preparation method thereof

By using components such as SEBS, EVM and maleic anhydride graft polymers in the thermoplastic elastomer composition, the problem of poor bonding performance between thermoplastic elastomer and PVC is solved, and better interface compatibility and bonding strength are achieved, ensuring long-term stability and high pressure adaptability of the sealing ring.

CN119798833AActive Publication Date: 2025-04-11NINGBO HANJI POLYMER MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510287644.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The bonding performance of thermoplastic elastomers and PVCs is poor, which makes it difficult to maintain the sealing state when used for a long time or withstands large pressures.

Method used

The soft thermoplastic elastomer composition is prepared using components such as SEBS, EVM, SEBS-g-MAH, POE-g-MAH, etc., and is extruded and granulated through a twin-screw extruder to enhance the interface compatibility between the composition and PVC.

Benefits of technology

The bonding strength and compatibility between the thermoplastic elastomer and PVC is significantly improved, ensuring that the sealing ring can remain in a tight sealing state under long-term use and high pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a soft thermoplastic elastomer composition and a preparation method thereof. The soft thermoplastic elastomer composition is prepared from the following components in parts by weight: 20 parts of SEBS (Styrene-Ethylene-Butylene-Styrene), 40 to 60 parts of EVM (Ethylene Vinyl Acetate), 10 to 15 parts of compatilizer, 10 to 20 parts of white oil, 0 to 15 parts of filler, 0.1 to 1 part of lubricant, 0.5 part of antioxidant, 0.5 part of anti-UV (Ultraviolet) agent and 0.5 to 3 parts of coloring agent, and the compatilizer comprises SEBS-g-MAH (Styrene-Ethylene-Butylene-Styrene) and POE-g-MAH (Polyolefin Elastomer-g-MAH). The thermoplastic elastomer composition is prepared by taking SEBS-g-MAH and POE-g-MAH as compatilizers and matching with SEBS, EVM and other components, and the adhesive property can be effectively improved on the basis of maintaining the elasticity of the thermoplastic elastomer composition, so that the thermoplastic elastomer composition is more suitable for being prepared into the PVC corrugated hose end sealing ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a soft thermoplastic elastomer composition and a preparation method thereof. Background Art

[0002] PVC corrugated hoses are widely used in household appliances such as vacuum cleaners and washing machines due to their good flexibility and corrosion resistance. In order to ensure that the PVC corrugated hose is tightly and firmly connected to other parts of the equipment, the use of sealing rings at the ends of the PVC corrugated hoses is particularly important.

[0003] At present, the mainstream PVC corrugated hose end seal injection molding material on the market is soft PVC. Since both soft PVC and PVC corrugated hose are PVC materials generated by polymerization of vinyl chloride monomer, soft PVC and PVC corrugated hose have similar chemical structures and physical properties, good compatibility and certain bonding effects. In actual use, due to the strong polarity of chlorine atoms in the PVC molecular chain, there is a strong interaction force between the molecular chains of PVC, which makes the PVC material rigid. Although soft PVC is modified by adding plasticizers, soft PVC still retains a certain rigidity, so the elasticity of soft PVC is relatively poor, and it is difficult to maintain a tight sealing state when used for a long time or under high pressure.

[0004] In view of the above-mentioned prior art, the inventors believe that thermoplastic elastomer has excellent elasticity and flexibility, which makes it difficult for it to lose its elastic effect due to deformation, and is a good substitute for soft PVC. However, since thermoplastic elastomer is copolymerized by multiple monomers, its molecular chain contains non-polar or weakly polar segments, and the number and distribution of polar functional groups are relatively uneven, resulting in the thermoplastic elastomer being non-polar or weakly polar as a whole, while the molecular chain of PVC contains strongly polar chlorine atoms, which makes its molecular chain show strong polarity. The polarity difference between the two is large. According to the principle of like dissolves like, the interaction force between the two is weak, resulting in poor bonding performance between thermoplastic elastomer and PVC. Summary of the invention

[0005] In order to solve the problem of poor bonding performance between thermoplastic elastomer and PVC, the present application provides a soft thermoplastic elastomer composition and a preparation method thereof, wherein the soft thermoplastic elastomer composition has excellent bonding performance with PVC.

[0006] In a first aspect, the present application provides a soft thermoplastic elastomer composition, which adopts the following technical solution: A soft thermoplastic elastomer composition comprises the following components in parts by weight: 20 parts of SEBS, 40-60 parts of EVM, 10-15 parts of a compatibilizer, 10-20 parts of white oil, 0-15 parts of a filler, 0.1-1 parts of a lubricant, 0.5 parts of an antioxidant, 0.5 parts of an anti-UV agent, and 0.5-3 parts of a colorant, wherein the compatibilizer comprises SEBS-g-MAH and POE-g-MAH.

[0007] By adopting the above technical scheme, SEBS is a thermoplastic elastomer with a special structure, and its molecular chain contains a hard segment (styrene block) and a soft segment (ethylene-butylene block), and the soft segment gives SEBS good elasticity; ethylene-vinyl acetate rubber (EVM) is a polar rubber, and its molecular chain contains vinyl acetate groups. The polarity of vinyl acetate groups is similar to that of PVC, which can increase the polar interaction force between EVM and PVC, thereby improving the interface compatibility; SEBS-g-MAH is obtained by grafting maleic anhydride onto the SEBS molecular chain. Maleic anhydride is a functional group with strong polarity, which can form hydrogen bonds or dipole-dipole interactions with chlorine atoms in the PVC molecular chain, thereby enhancing the interface compatibility between SEBS and PVC. At the same time, the similar hydrocarbon backbone between the POE chain and EVM makes POE-g-MAH and EVM compatible.

[0008] When the thermoplastic elastomer composition in a molten state comes into contact with the end of the PVC corrugated hose, the PVC corrugated hose receives heat and melts slightly; the vinyl acetate groups in the EVM can form polar interactions with the chlorine atoms in the PVC molecular chain, increasing the intermolecular forces at the interface; at the same time, SEBS-g-MAH can act as a "bridge" to enhance the interaction between SEBS and PVC; POE-g-MAH can act as a "bridge" to further enhance the interaction between EVM and PVC, significantly improving the bonding strength between them.

[0009] Optionally, the mass ratio of SEBS to SEBS-g-MAH is 20:8-10.

[0010] By adopting the above technical solution, when the content of SEBS-g-MAH is too low, the effect of SEBS-g-MAH as a "bridge" to enhance the interaction between SEBS and PVC is weak, and the effect of improving the bonding performance is not obvious; when the content of SEBS-g-MAH is too high, the content of SEBS-g-MAH is sufficient to achieve the connection between SEBS and PVC, and no further addition is required; for this reason, the applicant finally determined after a lot of research and experimental verification that the mass ratio of SEBS and SEBS-g-MAH in this application is preferably the above.

[0011] Optionally, the compatibilizer further comprises catechol.

[0012] By adopting the above technical solution, the hydroxyl groups in the catechol molecular structure can produce an esterification reaction with the anhydride groups in SEBS-g-MAH and POE-g-MAH to form an ester bond, thereby realizing the connection between catechol and maleic anhydride. At the same time, due to the structural similarity between the benzene ring in catechol and the styrene block of SEBS, the compatibility between catechol and SEBS is good; at the same time, the hydroxyl groups in the catechol molecular structure can absorb the hydrogen chloride gas generated during the degradation of PVC, thereby delaying the degradation of PVC.

[0013] Optionally, the mass ratio of SEBS to catechol is 20:0.1-0.3.

[0014] By adopting the above technical solution, when the catechol content is too low, the number of hydroxyl groups in the thermoplastic elastomer composition is limited and cannot fully react with the anhydride groups in SEBS-g-MAH and POE-g-MAH, so that catechol cannot be evenly dispersed in SEBS, and the compatibility of the thermoplastic elastomer composition is slightly affected. At the same time, the hydroxyl groups of the catechol molecules absorb hydrogen chloride, and the effect of inhibiting the degradation of PVC is not obvious. Although catechol can improve the compatibility of SEBS and other components in the thermoplastic elastomer composition, when the catechol content is too high, the hydroxyl groups introduced into the thermoplastic elastomer composition are sufficient to fully react with the anhydride groups, and too much catechol will also reduce the economic efficiency of the thermoplastic elastomer composition. For this reason, the applicant finally determined after a lot of research and experimental verification that the mass ratio of SEBS and catechol in the present application is preferably as above.

[0015] Optionally, the VA content of the EVM is in the range of 50-65wt%.

[0016] By adopting the above technical scheme, when the vinyl acetate (VA) content in EVM is high, the polar VA side groups in the EVM molecular chain give the material good elasticity and flexibility; as the VA content increases, the polarity in the EVM molecular chain increases, and since the polarities of EVM and PVC are similar, the compatibility between EVM and PVC is further improved; but excessive VA will destroy the crystalline area formed by the polyethylene chain segment, resulting in a decrease in crystallinity, thereby causing a decrease in the elastic properties of EVM; for this reason, the applicant finally determined after a lot of research and experimental verification that the VA content of the EVM of this application is preferably within the above range.

[0017] Optionally, the filler is activated calcium carbonate.

[0018] By adopting the above technical scheme, the surface of activated calcium carbonate as an inorganic filler is modified to have active groups such as hydroxyl and carboxyl. These active groups such as hydroxyl can form hydrogen bonds with the maleic anhydride groups in the compatibilizer, thereby enhancing the compatibility between the filler and the various components of the thermoplastic elastomer composition. The long hydrocarbon chains on the surface of the activated calcium carbonate particles may also be physically entangled with the soft segment part in the SEBS molecular chain; at the same time, the polar groups such as hydroxyl and carboxyl on the surface of the activated calcium carbonate particles can form hydrogen bonds with the polar electron clouds near the polar chlorine atoms of the PVC molecules, thereby significantly improving the bonding force between the calcium carbonate and the PVC molecular chain, and further enhancing the bonding performance between the thermoplastic elastomer composition and the PVC corrugated hose.

[0019] Optionally, the particle size of the activated calcium carbonate is in the range of 2000-2500 mesh.

[0020] By adopting the above technical solution, when the particle size of the activated calcium carbonate is small, it can be dispersed more evenly in the thermoplastic elastomer composition, reducing the stress concentration points caused by particle agglomeration, which helps to improve the overall uniformity and compatibility of the thermoplastic elastomer composition; at the same time, the uniform dispersion of the activated calcium carbonate also helps to form a denser interface layer between the thermoplastic elastomer composition and PVC, reducing the gaps and defects at the interface, and further improving the tightness and stability of the bonding; However, when the particle size of the activated calcium carbonate is too small, it may cause agglomeration of the activated calcium carbonate in the thermoplastic elastomer composition, which in turn reduces the overall uniformity and compatibility of the thermoplastic elastomer composition. For this reason, the applicant has finally determined after a lot of research and experimental verification that the particle size of the activated calcium carbonate in the present application is preferably within the above range.

[0021] In a second aspect, the present application provides a method for preparing a soft thermoplastic elastomer composition, using the following technical solution: A method for preparing a soft thermoplastic elastomer composition is used to prepare the soft thermoplastic elastomer composition, comprising the following steps: adding a formula amount of SEBS, a compatibilizer, EVM and other processing aids into a mixer, mixing them evenly and then accurately measuring them using a loss-in-weight scale, then feeding them into a twin-screw extruder for extrusion granulation, and obtaining the soft thermoplastic elastomer composition after pelletizing.

[0022] By adopting the above technical solution, the present application adopts a mixing method to prepare a soft thermoplastic elastomer composition. The preparation method is simple and the content of each component is accurately measured, so that the prepared soft thermoplastic elastomer composition has excellent bonding properties with PVC.

[0023] Optionally, the main engine speed of the twin-screw extruder is 400-600rpm.

[0024] By adopting the above technical solution, the twin-screw extruder can effectively mix SEBS, compatibilizer, EVM and other processing aids through its special screw design and speed control; when the speed is too low, it may cause uneven mixing of the components, and when the speed is too high, the structure of the material may be destroyed due to excessive shearing.

[0025] Optionally, the granulation temperature range of the twin-screw extruder is 160-180°C.

[0026] By adopting the above technical solution, temperature is an important parameter in plastic processing, which directly affects the melting state, fluidity and viscosity of the material. When the temperature is too low, SEBS-g-MAH cannot be fully melted, making it difficult to fully exert the effect of the compatibilizer, resulting in uneven mixing and even irregular particles and breakage. When the temperature is too high, the polymer is prone to thermal degradation and oxidation reactions, leading to problems such as molecular chain breakage and performance degradation; for the compatibilizer, too high a temperature will cause it to decompose, affecting its bonding effect with PVC.

[0027] In summary, this application has the following beneficial effects: 1. The present application adopts SEBS-g-MAH and POE-g-MAH as compatibilizers to prepare a thermoplastic elastomer composition in combination with SEBS and EVM and other components, which can effectively improve the bonding performance while maintaining its elasticity, so that it is more suitable for preparing a PVC corrugated hose end seal ring; 2. The application adds catechol to the compatibilizer, which can form an ester bond with the maleic anhydride group in the compatibilizer and thus be evenly dispersed in SEBS, further improving the compatibility between SEBS and other components. At the same time, catechol can also absorb hydrogen chloride gas and delay the degradation of PVC. DETAILED DESCRIPTION

[0028] The raw materials in this application include the following parts: SEBS: a commercially available product is used. This application uses the SEBS of model YH-502T produced by Shanghai Baling Petrochemical Co., Ltd. as an example; EVM: This application is described by taking the models Levapren 450 (VA content 45wt%), Levapren 500 (VA content 50wt%), Levapren 600 (VA content 60wt%), Levapren 650VP (VA content 65wt%), and Levapren 700 (VA content 70wt%) produced by ARLANXEO High Performance Elastomers (Changzhou) Co., Ltd. as examples; SEBS-g-MAH: a commercially available product with the brand name Taipol-7126; POE-g-MAH: a commercially available product with the brand name M2265 was used; Catechol: a commercially available product with CAS number 120-80-9 was used; Filler: This application is described by taking activated calcium carbonate with the grades of Js-1500 (particle size 1500 mesh), Js-2000 (particle size 2000 mesh), HX-2500 (particle size 2500 mesh), BR-3000 (particle size 3000 mesh), silica powder with the grade of FSCJZX-2000, and talc powder with the grade of KH-206 as examples; White oil: This application uses a commercial product with CAS number 8042-47-5; Lubricant: polyethylene wax, fatty acid and its salts, etc. This application takes polyethylene wax, a commercial product with CAS number 9002-88-4, as an example for explanation; Antioxidant: This application takes antioxidant 1010 as an example for explanation; Anti-UV agent: This application takes the anti-UV agent UV-944 as an example for explanation; Colorant: carbon black, color powder, etc. This application takes carbon black, a commercial product with CAS number 1333-86-4, as an example for explanation; The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0029] Example 1 A method for preparing a soft thermoplastic elastomer composition comprises the following steps: 20 kg of SEBS, 50 kg of EVM (Levapren 600), 5 kg of SEBS-g-MAH, 8 kg of POE-g-MAH, 8 kg of activated calcium carbonate (Js-2000), 15 kg of white oil, 0.5 kg of lubricant, 0.5 kg of antioxidant, 0.5 kg of anti-UV agent and 1.5 kg of colorant were added into a high-speed mixer and mixed at 600 rpm for 10 min to obtain a uniform mixture.

[0030] The mixture is added to a twin-screw extruder for melt kneading, and then the molten material is extruded. The main engine speed of the twin-screw extruder is 500 rpm, and the extrusion temperature is 170° C. After the extruded molten material is cooled and pelletized, a soft thermoplastic elastomer composition is obtained.

[0031] Example 2-3 Example 2-3 Based on the preparation method of Example 1, the content of each component of the soft thermoplastic elastomer composition was adjusted. The specific adjustments are shown in Table 1.

[0032] Comparative Examples 1-3 Comparative Examples 1-3 Based on the preparation method of Example 1, the content of each component of the soft thermoplastic elastomer composition was adjusted, and the specific adjustments are shown in Table 1.

[0033] Table 1 Compositions and performance test table of the soft thermoplastic elastomer compositions of Examples 1-3 and Comparative Examples 1-3

[0034] Performance testing The soft thermoplastic elastomer compositions of Examples 1-3 and Comparative Examples 1-3 were sampled and analyzed. The preparation and testing methods are as follows: (1) Tensile strength and elongation at break The soft thermoplastic elastomer compositions prepared as above were weighed respectively, and placed in a rectangular mold frame with a thickness of 4 mm. The mold frame was placed between the upper and lower plates of a rubber flat vulcanizer. The temperature of the upper and lower plates was set to 210°C. After maintaining the pressure at 10 MPa for 5 minutes, the mold frame was taken out and cooled naturally, and soft thermoplastic elastomer composition samples with a thickness of 4 mm were obtained respectively.

[0035] The soft thermoplastic elastomer composition samples provided in Examples 1-3 and Comparative Examples 1-3 of the present application were tested for tensile strength and elongation at break of the soft thermoplastic elastomer composition according to ISO37 standard, and the test results are shown in Table 1. Sample size: 80mm*10mm*4mm, dumbbell shape, tensile speed is 500mm / min.

[0036] (2) PVC bonding peel strength A layer of silicone oil was evenly applied as an isolation agent in an area of ​​50 mm in width at one end of the surface of a PVC test piece with a thickness of 2 mm. The PVC test piece coated with silicone oil was placed in a rectangular mold frame with a thickness of 3 mm. The soft thermoplastic elastomer compositions prepared as above were weighed respectively, and injection molding was performed on the surface of the test piece. The injection molding temperature was set to 210°C so that the injection molding material evenly covered the surface of the test piece to form an injection molding layer with a thickness of 1 mm. The injection molded test piece was placed in a laboratory environment, the ambient temperature was adjusted to maintain for 12 hours, and then it was cut into test samples with a specification of 150 mm*10 mm.

[0037] The soft thermoplastic elastomer composition samples provided in Examples 1-3 of the present application and Comparative Examples 1-3 were separated from one end coated with a release agent, and the samples on both sides of the release agent were clamped on the upper and lower clamps of a universal testing machine, respectively. The universal testing machine was started to apply a peeling force until the sample was damaged, and the ratio of the peeling force and the sample width was calculated to obtain the PVC adhesive peeling strength. The test results are shown in Table 1.

[0038] As shown in Table 1, SEBS-g-MAH has an effect on the bonding performance of the soft thermoplastic elastomer composition and PVC, which may be due to the SEBS chain and MAH chain of SEBS-g-MAH interacting with SEBS and PVC respectively, connecting the two; POE-g-MAH has an effect on the bonding performance of the soft thermoplastic elastomer composition and PVC, which may be due to the interaction between POE-g-MAH and EVM and PVC respectively, strengthening the connection between the two; In addition, a comprehensive comparison of Examples 1-3 and Comparative Examples 1-3 shows that the soft thermoplastic elastomer composition of Example 1 has the best elasticity and adhesion to PVC, so Example 1 is preferred.

[0039] Embodiment 4-5 Example 4-5 Based on the preparation method of Example 1, the content of SEBS-g-MAH was adjusted, and the specific adjustment is shown in Table 2.

[0040] Comparative Examples 4-5 Comparative Example 4-5 Based on the preparation method of Example 1, the content of SEBS-g-MAH was adjusted, and the specific adjustment is shown in Table 2.

[0041] The soft thermoplastic elastomer compositions of Examples 4-5 and Comparative Examples 4-5 were subjected to the above performance tests. The test results are shown in Table 2.

[0042] Table 2 Addition amount and performance test data of SEBS-g-MAH in Example 1, Examples 4-5 and Comparative Examples 4-5

[0043] Referring to Table 2, by comparing Example 1, Examples 4-5 and Comparative Examples 4-5, it can be seen that with the increase in the amount of SEBS-g-MAH added to the soft thermoplastic elastomer composition, the bonding performance of the soft thermoplastic elastomer composition with PVC is continuously enhanced. This may be because the interaction between SEBS-g-MAH, SEBS and PVC is continuously enhanced with SEBS-g-MAH, thereby improving the compatibility of the soft thermoplastic elastomer composition with PVC. In Example 1, the interaction between SEBS-g-MAH, SEBS and PVC reaches saturation.

[0044] Embodiment 6-8 In Examples 6-8, based on the preparation method of Example 1, the content of catechol was adjusted. The specific adjustments are shown in Table 3.

[0045] Comparative Examples 6-7 Comparative Example 6-7 is based on the preparation method of Example 1, and the content of catechol is adjusted. The specific adjustment is shown in Table 3.

[0046] The soft thermoplastic elastomer compositions of Examples 6-7 and Comparative Examples 6-7 were prepared and analyzed. The preparation and testing methods are as follows: A layer of silicone oil was evenly applied as an isolation agent in an area of ​​50 mm in width at one end of the surface of a PVC test piece with a thickness of 2 mm. The PVC test piece coated with silicone oil was placed in a rectangular mold frame with a thickness of 3 mm. The soft thermoplastic elastomer compositions prepared as above were weighed respectively, and injection molding was performed on the surface of the test piece. The injection molding temperature was set to 210°C so that the injection molding material evenly covered the surface of the test piece to form an injection molding layer with a thickness of 1 mm. The injection molded test piece was placed in a laboratory environment, the ambient temperature was adjusted to maintain for 12 hours, and then it was cut into test samples with a specification of 150 mm*10 mm.

[0047] In accordance with the national standard GB / T16422.2-2022, the above-mentioned test samples were placed in a xenon lamp aging test chamber. The temperature of the test chamber was set to 60±3°C in light and 50±3°C in darkness. The humidity was set to 50%±5% in light and 70%±5% in darkness. The exposure cycle was 8 hours in light and 4 hours in darkness. After 48 hours, samples were taken for the above-mentioned PVC adhesive peel strength test, and the change rate of PVC adhesive peel strength before and after aging treatment was calculated.

[0048] The soft thermoplastic elastomer compositions of Example 1, Examples 6-7 and Comparative Examples 6-7 were subjected to the above performance tests. The test results are shown in Table 3.

[0049] Table 3 The amount of catechol added and the performance test data of Example 1, Examples 6-8 and Comparative Examples 6-7

[0050] Referring to Table 3, it can be seen from the comparison of Example 1, Examples 6-8 and Comparative Examples 6-7 that, as the amount of catechol added increases, the elastic properties of the soft thermoplastic elastomer and the adhesion properties to PVC show a trend of increasing and then leveling off. This may be because, as the content of catechol increases, catechol continuously reacts with the anhydride group, thereby enhancing the compatibility between the components of the thermoplastic elastomer composition; when the amount of catechol added exceeds a certain range, the anhydride group and catechol fully react, and the effect of improving compatibility approaches saturation.

[0051] In addition, as the amount of catechol added continued to increase, the values ​​of the change rate of the PVC bonding peel strength of the soft thermoplastic elastomer continued to decrease. This may be because catechol continued to absorb the hydrogen chloride gas produced by the degradation of PVC, thereby delaying the degradation of the PVC injection molding surface.

[0052] In addition, by comprehensively comparing Example 1, Examples 6-8 and Comparative Examples 6-7, it is found that the soft thermoplastic elastomer composition of Example 8 has the best elasticity and adhesion performance with PVC, so Example 8 is preferred.

[0053] Examples 9-10 Example 9 Based on the preparation method of Example 8, the model of EVM is changed from Levapren 600 (VA content 60%) to Levapren 500 (VA content 50%).

[0054] Example 10 Based on the preparation method of Example 8, the model of EVM is changed from Levapren 600 (VA content 60%) to Levapren 650VP (VA content 65%).

[0055] Comparative Examples 8-9 Comparative Example 8: Based on the preparation method of Example 8, the type of EVM is changed from Levapren 600 (VA content 60%) to Levapren 450 (VA content 45%).

[0056] Comparative Example 9: Based on the preparation method of Example 8, the type of EVM was changed from Levapren 600 (VA content 60%) to Levapren 700 (VA content 70%).

[0057] The soft thermoplastic elastomer compositions of Examples 9-10 and Comparative Examples 8-9 were subjected to the above performance tests. The test results are shown in Table 4.

[0058] Table 4 Performance test data table of Example 8, Examples 9-10 and Comparative Examples 8-9

[0059] Referring to Table 4, it can be seen from the comparison of Example 8, Examples 9-10 and Comparative Examples 8-9 that as the VA content of EVM continues to increase, the tensile strength and elongation at break of the soft thermoplastic elastomer composition continue to increase and then decrease. This may be due to the presence of excessive VA destroying the crystalline region formed by the polyethylene chain segment, resulting in a decrease in crystallinity, thereby affecting the tensile strength and elongation at break of the soft thermoplastic elastomer composition; at the same time, the bonding performance of the soft thermoplastic elastomer composition with PVC continues to improve, which may be due to the increase in polar VA side groups in the EVM molecular chain further enhancing the compatibility between EVM and PVC.

[0060] Comparative Examples 10-11 Comparative Example 10 is based on the preparation method of Example 8, except that the activated calcium carbonate is replaced with silicon powder.

[0061] Comparative Example 11 is based on the preparation method of Example 8, except that the activated calcium carbonate is replaced with talc.

[0062] The soft thermoplastic elastomer compositions of Comparative Examples 10-11 were subjected to the above performance tests, and the test results are shown in Table 5.

[0063] Table 5 Performance test data table of Example 8 and Comparative Examples 10-11

[0064] Referring to Table 5, it can be seen from the comparison of Example 8 and Comparative Examples 10-11 that, compared with the soft elastomer composition of Example 1, the elasticity and adhesive properties of the soft thermoplastic elastomer composition of Comparative Examples 10-11 are lower than those of the soft thermoplastic elastomer composition of Example 1, which indicates that activated calcium carbonate is a preferred filler for the soft thermoplastic elastomer composition.

[0065] Embodiment 11

[0066] Example 11 Based on the preparation method of Example 8, the brand of activated calcium carbonate is changed from Js-2000 (particle size 2000 mesh) to Hx-2500 (particle size 2500 mesh).

[0067] Comparative Examples 12-13 Comparative Example 12: Based on the preparation method of Example 8, the brand of activated calcium carbonate is changed from Js-2000 (particle size 2000 mesh) to Js-1500 (particle size 1500 mesh).

[0068] Comparative Example 13 Based on the preparation method of Example 8, the grade of activated calcium carbonate was changed from Js-2000 (particle size 2000 mesh) to BR-3000 (particle size 3000 mesh). The soft thermoplastic elastomer compositions of Example 11 and Comparative Example 12 were subjected to the above performance tests. The test results are shown in Table 6.

[0069] Table 6 Performance test data table of Example 8, Example 11 and Comparative Examples 12-13

[0070] Referring to Table 6, it can be seen from Example 8, Example 11 and Comparative Examples 12-13 that as the particle size of the activated calcium carbonate continues to decrease, the elasticity and bonding properties of the soft thermoplastic elastomer composition continue to increase and then decrease. This may be because the activated calcium carbonate with a small particle size can be dispersed more evenly in the soft thermoplastic elastomer, thereby enhancing the bonding effect between the soft thermoplastic elastomer composition and PVC; when the particle size of the activated calcium carbonate is smaller than a certain range, the activated calcium carbonate begins to agglomerate in the soft thermoplastic elastomer composition, thereby affecting the bonding performance of the soft thermoplastic elastomer composition and PVC.

[0071] Examples 12-13 In Examples 12-13, based on the preparation method of Example 1, the main engine speed of the twin-screw extruder was adjusted, and the specific adjustments are shown in Table 7.

[0072] Comparative Examples 14-15 Comparative Examples 14-15 are based on the preparation method of Example 1, and the main engine speed of the twin-screw extruder is adjusted. The specific adjustments are shown in Table 7.

[0073] The soft thermoplastic elastomer compositions of Examples 12-13 and Comparative Examples 14-15 were subjected to the above performance tests. The test results are shown in Table 7.

[0074] Table 7 Main engine speed and performance test data table of Example 1, Examples 12-13 and Comparative Examples 14-15

[0075] Referring to Table 7, it can be seen from the comparison of Example 1, Examples 12-13 and Comparative Examples 14-15 that, compared with the soft thermoplastic elastomer compositions of Examples 1 and 12-13, the elastic properties and the bonding properties with PVC of the soft thermoplastic elastomer compositions of Comparative Examples 14-15 are much lower than those of the soft thermoplastic elastomers of Examples 1 and 12-13; this may be due to the uneven mixing of the components when the main engine speed is too slow, and the excessive shearing when the main engine speed is too high, which destroys the structure of the thermoplastic composition, thereby resulting in a decrease in the bonding performance of the thermoplastic elastomer composition with PVC.

[0076] Examples 14-15 In Examples 14-15, based on the preparation method of Example 1, the extrusion temperature of the twin-screw extruder was adjusted, and the specific adjustments are shown in Table 8.

[0077] Comparative Examples 16-17 In Comparative Examples 16-17, based on the preparation method of Example 1, the extrusion temperature of the twin-screw extruder was adjusted, and the specific adjustments are shown in Table 8.

[0078] The soft thermoplastic elastomer compositions of Examples 14-15 and Comparative Examples 16-17 were subjected to the above performance tests. The test results are shown in Table 8.

[0079] Table 8 Extrusion temperature and performance test data of Example 1, Examples 14-15 and Comparative Examples 16-17

[0080] Referring to Table 8, it can be seen from the comparison of Example 1, Examples 14-15 and Comparative Examples 16-17 that compared with the soft thermoplastic elastomer compositions of Examples 1 and Examples 14-15, the bonding properties of the soft thermoplastic elastomer compositions of Comparative Examples 16-17 to PVC are much lower than those of the soft thermoplastic elastomers of Examples 1 and Examples 16-17.

[0081] This may be because when the extrusion temperature is too low, some components in the soft thermoplastic elastomer composition are not completely melted, resulting in uneven mixing of the components; when the extrusion temperature is too high, some components in the soft thermoplastic elastomer composition are decomposed, thereby affecting the elasticity of the soft thermoplastic elastomer composition and its bonding performance with PVC.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but such modifications are protected by patent law as long as they are within the scope of the claims of the present application.

Claims

1. A soft thermoplastic elastomer composition, characterized in that: The invention comprises the following components in parts by weight: 20 parts of SEBS, 40-60 parts of EVM, 10-15 parts of compatibilizer, 10-20 parts of white oil, 0-15 parts of filler, 0.1-1 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-UV agent and 0.5-3 parts of colorant, wherein the compatibilizer comprises SEBS-g-MAH and POE-g-MAH.

2. The soft thermoplastic elastomer composition according to claim 1, characterized in that: The mass ratio of the SEBS to the SEBS-g-MAH is 20:8-10.

3. The soft thermoplastic elastomer composition according to claim 1, characterized in that: The compatibilizer also includes catechol.

4. The soft thermoplastic elastomer composition according to claim 3, characterized in that: The mass ratio of SEBS to catechol is 20:0.1-0.

3.

5. The soft thermoplastic elastomer composition according to claim 1, characterized in that: The VA content of the EVM is in the range of 50-65 wt %.

6. The soft thermoplastic elastomer composition according to claim 1, characterized in that: The filler is activated calcium carbonate.

7. The soft thermoplastic elastomer composition according to claim 6, characterized in that: The particle size of the activated calcium carbonate is in the range of 2000-2500 mesh.

8. The method for preparing the soft thermoplastic elastomer composition according to any one of claims 1 to 7, characterized in that: The formulated amount of SEBS, compatibilizer, EVM and other processing aids are added into a mixer, mixed evenly, accurately measured by a loss-in-weight scale, and then fed into a twin-screw extruder for extrusion granulation, and the soft thermoplastic elastomer composition is obtained after pelletizing.

9. The method for preparing a soft thermoplastic elastomer composition according to claim 8, characterized in that: The main engine speed of the twin-screw extruder is 400-600rpm.

10. The method for preparing a soft thermoplastic elastomer composition according to claim 8, characterized in that: The granulation temperature range of the twin-screw extruder is 160-180°C.

Citation Information

Patent Citations

  • Thermoplastic elastomer composition for bonding PA and preparation method thereof

    CN101747576A

  • Thermochromic thermoplastic elastomer (TPE) with V0 flame-retardant grade and preparation method thereof

    CN109851922A

  • TPE alloy for polyphenyl ether bonding encapsulation as well as preparation method and application of TPE alloy

    CN112759886A

  • Low-temperature-resistant low-smoke halogen-free flame-retardant cable material and preparation method thereof

    CN115746443A

  • TPU composite material melt-blown film, preparation method and laminated composite TPU fabric of TPU composite material melt-blown film

    CN117306095A